2018
DOI: 10.31234/osf.io/tdbne
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Can joint action goals reduce visuomotor interference effects from a partner’s incongruent actions?

Abstract: Joint actions often require agents to track others’ actions while planning and executing physically incongruent actions of their own. Previous research has indicated that this can lead to visuomotor interference effects when it occurs outside of joint action. How is this avoided or overcome in joint actions? We hypothesized that when joint action partners represent their actions as interrelated components of a plan to bring about a joint action goal, each partner’s movements need not be represented in relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Thus, we show that TPJ is necessary to synchronize and anticipate imitative interactions. Importantly, that interfering with the activity of rTPJ did not compromise the ability to perform complementary interactions supports the idea that complementary interactions, in which co-actors need to predict and integrate each other's actions in order to achieve a shared goal, do not require the control of self-other representations, needed instead in conditions in which coactors perform actions at the same time, one independently from the other (Clarke et al, 2018;. Our results show, instead, that TPJ activity supports the ability to perform imitative interactions, where a direct mapping of the observed action onto one's own motor representation is needed.…”
Section: Role Of the Tpj For Imitative Interactionsmentioning
confidence: 67%
See 1 more Smart Citation
“…Thus, we show that TPJ is necessary to synchronize and anticipate imitative interactions. Importantly, that interfering with the activity of rTPJ did not compromise the ability to perform complementary interactions supports the idea that complementary interactions, in which co-actors need to predict and integrate each other's actions in order to achieve a shared goal, do not require the control of self-other representations, needed instead in conditions in which coactors perform actions at the same time, one independently from the other (Clarke et al, 2018;. Our results show, instead, that TPJ activity supports the ability to perform imitative interactions, where a direct mapping of the observed action onto one's own motor representation is needed.…”
Section: Role Of the Tpj For Imitative Interactionsmentioning
confidence: 67%
“…We have previously shown in the same experimental set-up used in the present study that synchronization during complementary and imitative interactions do not differ (Sacheli et al, 2012;Sacheli et al, 2013;Sacheli et al, 2015;Era et al, 2018) supporting the idea that at a performance level, during an interactive task, complementing and imitating the action of a partner are not affected by automatic imitation. Moreover, recent studies demonstrated that automatic imitation is reduced when two different executed and observed actions are interdependent in contributing to a shared goal (Clarke et al, 2018). Hogeveen et al, 2015 have shown that anodal tDCS applied to right TPJ reduces the tendency to imitate, task irrelevant, finger movements incongruent with those that participants had to perform, but that this inhibition does not appear in more ecological tasks.…”
Section: Role Of the Tpj For Imitative Interactionsmentioning
confidence: 99%
“…In terms of online interference, participants’ motor performance is less affected when they have to interact in a joint task with respect to an isolated context (Sacheli, Arcangeli & Paulesu, 2018). In other circumstances, however, the interference due to physical incongruence is only partially decreased (Clarke et al, 2018)—or even increased (Della Gatta et al, 2017)—by the joint goal. For instance, when participants have to draw circles or lines with their right hands while observing on the screen the circles or lines that are simultaneously drawn by a partner, this leads to an increase—rather than a decrease—in interference effects during the Joint Action condition.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, less interference occurs for a “second task” if the primary task is automatized (Castiello & Umiltà, 1987; Castiello, 1996; Guillery, Mouraux & Thonnard, 2013). Indeed, while the task in Sacheli, Arcangeli & Paulesu (2018) was well learnt after a training phase of 20 min, Clarke et al (2018) participants performed only four trials before each block, and no training at all was performed by Della Gatta et al (2017). When a particular stimulus–response pair is well learnt, a reduction in top-down control would indicate its automaticity over other less frequently experienced responses (Campbell & Cunnington, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of online interference, participants' motor performance is less affected when they have to interact in a joint task with respect to an isolated context (Sacheli et al, 2018). In other circumstances, however, the interference due to physical incongruence is only partially decreased (Clarke et al, 2018) -or even increased (della Gatta et al 2017) -by the joint goal.…”
Section: The Continuum Hypothesismentioning
confidence: 99%